Antibiofilm activity of Oxytetracycline loaded calcium carbonate aragonite loaded nanoparticle against Corynebacterium Pseudotuberculosis - Banke, Idris Sherifat; Abdul Kadir, Arifah; Abdullah Jesse, Faez Firdaus; Ramanoon, Siti Zubaidah; Muhammad, Abdul Basit; Zakaria, Md Zuki Abu Bakar (Asian Network for Scientific Information (ANSINET), 2021)
Background and Objective: Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis, a zoonotic bacterial disease of small ruminants. The disease is unresponsive to antibiotic treatment due to the intracellular nature of the bacteria, thick purulent exudates, antibiotic resistance and formation of biofilms. The objective of this study was to evaluate the antibiofilm activity of oxytetracycline in free (OTC) and cockle shell loaded forms (OTC-CS-CaCO3NP) against C. pseudotuberculosis. Materials and Methods: The Minimum Inhibitory Concentration (MIC) and Minimum Biofilm Eradication Concentration (MBEC) of oxytetracycline in free and cockle shell loaded forms against C. pseudotuberculosis were determined by the microtiter plate assay method. Biofilm formation and inhibition assays were studied spectrophotometrically using the crystal violet assay method. TEM, SEM and fluorescent microscopy were used to assess the antibacterial and antibiofilm effect against C. pseudotuberculosis. Results: The MIC of OTC and OTC-CS-CaCO3NP against C. pseudotuberculosis were 125 and 500 μg L–1, respectively while the MBEC was 250 and >2000 μg L–1. TEM analysis showed OTC-CS-CaCO3NP disrupted cell membrane and formation of vacuoles in C. pseudotuberculosis. Conclusion: Microscopic analysis of the biofilms revealed OTC-CS-CaCO3NP caused significant morphological changes compared to OTC. These results suggest the potential applicability of OTC-CS-CaCO3NP for the treatment of caseous lymphadenitis.